Diagnostic Accuracy of Reverse Contrast Enhancement for Detection of Vertical Root Fractures - Sharifi shoshtari, Sanaz; Rahmani, Mona; Deimi, Mohamad; Alizad Rahvar, Maryam (Journal of Dental School, 2020)
Objectives Vertical root fracture (VRF) is a common complication in endodontically-treated teeth. Due to its poor prognosis, a valid and reliable detection method is imperative for treatment planning. The aim of this study was to evaluate the application of reverse contrast in diagnosis of VRF by digital radiography. Methods Fifty extracted single-rooted premolar teeth were selected for this in-vitro experimental study. The teeth were mounted in a dry mandible and fixed with wax. Radiographs were obtained of all teeth with 0° horizontal angle, and 0° and +15° vertical angle. VRFs were then created by a hammer in vertical direction. Radiographs were obtained again as previously described. Radiographs of each tooth were evaluated twice: once without reverse contrast and then with reverse contrast 2 weeks later. The weighted kappa coefficient was calculated to assess the inter-observer agreement. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+) and negative likelihood ratio (LR-) were compared in use and no use of reverse contrast using the Cochrane Q test. Results Radiographic angle had no significant effect on the diagnostic accuracy in use or no use of reverse contrast, except for the sensitivity value in no use of reverse contrast which was significantly higher in 15° vertical angle. The diagnostic accuracy of images enhanced with reverse contrast had no significant difference with original images in 0° and 15° vertical angles. Conclusion Radiographs enhanced with reverse contrast had no significant difference with original radiographs for diagnosis of VRFs. Thus, for detection of VRFs, reverse contrast should only be considered as an adjunct.